Analisis Pendapatan Usaha Kopra Pada Desa Lumahlatal Kecamatan Taniwel Timur Kabupaten Seram Bagian Barat - Kesaulya, Juliana; Elake, George (Journal of Applied Accounting, 2023)
Abstract Taniwel sub-district is one of the sub-districts in West Seram Regency (SBB). This region is also an economic center for the Maluku community but has not been supported by the availability of companies engaged in production so most agricultural products are sold out of the region. Agriculture is a very important and dominant sector in the life of the Indonesian people since before independence. Most of the population is in rural areas and relies on the agricultural sector. Food production to meet the needs of the community is almost entirely produced by smallholder agriculture. However, during the colonial period, smallholder agriculture did not progress much. This study aims to determine the income of copra farming in Lumahlatal Village, East Taniwel District, West Seram Regency. Data collection in this study used the observation method. Analytical techniques used in this study are descriptive, qualitative data, quantitative data are analyzed based on the distribution table of Lumahlatal Village. Then the income of respondents in the copra business was obtained amounting to Rp.7,875,000. Where the total revenue is Rp. 10,000,000 with an average total production cost of Rp.2,125,000. Keywords: income, business, production